"Pre-emption is victory": aggravated nuclear instability of the information age. Issue 5 (1st November 2016) - Austin, Greg; Sharikov, Pavel
ABSTRACT: Leading US military figures have discussed the use of pre-emptive cyberattack to disable or disrupt enemy nuclear missiles. While Russia does not appear to have such a highly developed concept, it now sees US plans to disrupt the command and control of its nuclear weapons as the main threat it faces at the strategic level of warfare. Cyberweapons and strategies have brought us to a situation of aggravated nuclear instability that needs to be more explicitly and openly addressed in the diplomacy of leading powers, both in private and in public. This article draws attention to a convergence between Russian interest in pre-emptive attack and reasonable views of Western strategists and scholars that the character of cyberspace favors offense and may encourage pre-emptive action. Since bilateral arms-control regimes for cyberspace are unlikely given the difficulty of verification and escalating US-Russian tension, states should commit to restraint regarding cyberattacks on nuclear military assets.